Is part‐night lighting an effective measure to limit the impacts of artificial lighting on bats?. (2nd November 2015) - Azam, Clémentine; Kerbiriou, Christian; Vernet, Arthur; Julien, Jean‐François; Bas, Yves; Plichard, Laura; Maratrat, Julie; Le Viol, Isabelle
Abstract: As light pollution is currently considered to be a major threat to biodiversity, different lighting management options are being explored to mitigate the impact of artificial lighting on wildlife. Although part‐night lighting schemes have been adopted by many local authorities across Europe to reduce the carbon footprint and save energy, their effects on biodiversity are unknown. Through a paired, in situ experiment, we compared the activity levels of 8 bat species under unlit, part‐night, and full‐night lighting treatments in a rural area located 60 km south of Paris, France. We selected 36 study locations composed of 1 lit site and a paired unlit control site; 24 of these sites were located in areas subject to part‐night lighting schemes, and 12 sites were in areas under standard, full‐night lighting. There was significantly more activity on part‐night lighting sites compared to full‐night lighting sites for the late‐emerging, light‐sensitive Plecotus spp., and a similar pattern was observable for Myotis spp., although not significant. In contrast, part‐night lighting did not influence the activity of early emerging bat species around streetlights, except for Pipistrellus pipistrellus for which there was significantly less activity on part‐night lighting sites than on full‐night lighting sites. Overall, no significant difference in activity between part‐ and full‐night lighting sites were observed in 5 of the 8 species studied, suggesting that current part‐night lighting schemes fail to encompass the range of activity of most bat species. We recommend that such schemes start earlier at night to effectively mitigate the adverse effects of artificial lighting on light‐sensitive species, particularly along ecological corridors that are especially important to the persistence of biodiversity in urban landscapes.